The Integration of the Second Generation in Germany: Results of the TIES Survey on the Descendants of Turkish and Yugoslavian Immigrants - Sürig, Inken (Amsterdam University Press, 2015)
This report on the German results of the Integration of the Second Generation in Europe (TIES) survey looks at the integration process for secondgeneration inhabitants of Turkish and Yugoslavian backgrounds living in Berlin and Frankfurt. Examining the TIES results, Inken Sürig and Maren Wilmes discuss diverse topics such as educational outcomes, segregation and housing, ethnic and cultural orientations, and social relations.